2002
DOI: 10.1002/dvdy.10205
|View full text |Cite
|
Sign up to set email alerts
|

Pronephric duct extension in amphibian embryos: Migration and other mechanisms

Abstract: Initiation of excretory system development in all vertebrates requires (1) delamination of the pronephric and pronephric duct rudiments from intermediate mesoderm at the ventral border of anterior somites, and (2) extension of the pronephric duct to the cloaca. Pronephric duct extension is the central event in nephric system development; the pronephric duct differentiates into the tubule that carries nephric filtrate out of the body and induces terminal differentiation of adult kidneys. Early studies concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…However, Drawbridge et al (Drawbridge et al, 1995) also showed that epidermal guidance cues are present throughout the tailbud stages of development and are therefore not responsible for the observed temporal restriction on PND migration (Poole and Steinberg, 1982;Gillespie and Armstrong, 1986). They proposed that two sets of guidance cues govern the timing and direction of PND migration: cues from the epidermis are required for directional information; and cues derived from lateral mesoderm are required to restrict migration temporally (Drawbridge et al, 1995;Drawbridge et al, 2003;Drawbridge and Steinberg, 1996). Therefore, a second model of PND guidance is also possible, in which laminin-requiring epidermal cues and mesodermally derived GDNF provide overlapping but independent sets of guidance information.…”
Section: Possible Models For Axolotl Pnd Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…However, Drawbridge et al (Drawbridge et al, 1995) also showed that epidermal guidance cues are present throughout the tailbud stages of development and are therefore not responsible for the observed temporal restriction on PND migration (Poole and Steinberg, 1982;Gillespie and Armstrong, 1986). They proposed that two sets of guidance cues govern the timing and direction of PND migration: cues from the epidermis are required for directional information; and cues derived from lateral mesoderm are required to restrict migration temporally (Drawbridge et al, 1995;Drawbridge et al, 2003;Drawbridge and Steinberg, 1996). Therefore, a second model of PND guidance is also possible, in which laminin-requiring epidermal cues and mesodermally derived GDNF provide overlapping but independent sets of guidance information.…”
Section: Possible Models For Axolotl Pnd Guidancementioning
confidence: 99%
“…PND elongation continues until the PND fuses with the cloaca, the exit point of the excretory system. In urodeles, including the axolotl Ambystoma mexicanum, as well as some primitive teleosts, PND morphogenesis appears to occur entirely by active cell migration accompanied by cell rearrangements (Ballard and Ginsburg, 1980;Poole and Steinberg, 1981;Poole, 1988;Drawbridge et al, 2003). Therefore, the events of axolotl PND morphogenesis provide an excellent system for studying directed cell migration in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In lef1 depleted embryos the pronephric ducts were absent or incomplete ( Figs 2E,H'). Expression of pax2, a marker for the pronephric tubules and pronephric duct (Heller and Brändli, 1997;Drawbridge et al, 2003) was absent posteriorly (Fig. 4F).…”
Section: Derivatives Of the Lateral Plate Mesoderm Are Absent Or Abnomentioning
confidence: 99%
“…During development, the Wolffian duct (WD) plays a major role in the formation of the accessory tissues (Drawbridge et al, 2003;Hannema and Hughes, 2007;Wilhelm et al, 2007). At the earliest stage of urogenital differentiation (E8.5-9.0) in the mouse, only pronephric components, which originate in the intermediate mesoderm, are observed in the urogenital tract.…”
Section: Introductionmentioning
confidence: 99%
“…During E15.5-16.5, gender specification occurs. The Müllerian duct degenerates in the male and production of androgenic hormones and hormone-like factors by the developing testes maintain tissues in the WD and mesonephric tubules (Capel, 2000;Cate et al, 1986), which differentiate into the epididymis, vas deferens, efferent ductules and seminal vesicles by E17.5 (Drawbridge et al, 2003;Hannema and Hughes, 2007;Ilio and Hess, 1994;Sainio and Raatikainen-Ahokas, 1999;Wilhelm et al, 2007).…”
Section: Introductionmentioning
confidence: 99%